Living with Heritage: Including tangible and intangible heritage in the changing time and space - Maharjan, Monalisa; Barata, Filipe Th. (Journal of the Institute of Engineering, 2018)
Kathmandu Valley, which now the compose of many cities and towns, is the result of centuries of evolution from small villages, hamlets and small towns. These cities evolved with the need and the lifestyle of people, a result of which gave birth to the magnificent art and architecture. The centuries old temples, squares, monuments, rest houses and water fountains are still present despite the frequent natural calamites like earthquake. The city which was once seemed to be designed for people and God now has to incorporate many things like population growth due to migration, urbanization, globalization and so on. The sudden influx of so-called “development” is putting the heritage and traditional values at risk. The integrated form of intangible heritage like rituals, festivals, mask dances and many more are the vehicle for the continuity of tangible heritage. But still in the heritage conservation practice, the focus has been on the tangible heritage. One of the major driving forces of heritage has been the indigenous people of Kathmandu Valley and the interconnectedness of their social life with the heritage. This paper is about the interrelationship with the tangible and intangible heritage in the changing dynamic of city, and how indigenous people are incorporating it concentrating only on Kathmandu city. This paper is based mostly on the field visit for the PhD of the author in 2014 and was initially presented in the conference Cultural Landscape and Heritage Values at University of Massachusetts, Amherst in 2015. Journal of the Institute of Engineering, 2017, 13(1): 178-189